Developing Adult Learners: A Model - Kathleen Taylor (Adult Education Research Conference, 2002)
Based on research with experienced adult educators, this framework for practice proposes a model of “developmental intentions” designed to encourage epistemological development in adult learners. This interactive session will also explore how developmental intentions can inform classroom strategies for teachers and trainers of adults.